Subclinical ochronosis features in alkaptonuria: a cross-sectional study. Issue 2 (28th September 2019) - Cox, Trevor; Psarelli, Eftychia Eirini; Taylor, Sophie; Shepherd, Hannah Rose; Robinson, Mark; Barton, Gabor; Mistry, Alpesh; Genovese, Federica; Braconi, Daniela; Giustarini, Daniela; Rossi, Ranieri; Santucci, Annalisa; et al.
Abstract : Background: Alkaptonuria (AKU) is present from birth, yet clinical effects are considered to appear later in life. Morbidity of AKU, considered irreversible, is secondary to ochronosis. Age of ochronosis onset is not clearly known. Nitisinone profoundly lowers homogentisic acid (HGA), the metabolic defect in AKU. Nitisinone also arrests ochronosis and slows progression of AKU. However, tyrosinaemia post-nitisinone has been associated with corneal keratopathy, rash and cognitive impairment in HT 1. The optimal time to start nitisinone in AKU is unknown. Methods: In an open, cross-sectional, single-site study, 32 patients with AKU were to be recruited. The primary outcome was presence of ochronosis in an ear biopsy. Secondary outcomes included analysis of photographs of eyes/ears, serum/urine HGA, markers of tissue damage/inflammation/oxidation, MRI imaging, gait, quality of life and Alkaptonuria Severity Score Index (qAKUSSI). Results: Thirty patients, with mean age (SD) 38 (14) years, were recruited. Percentage pigmentation within ear biopsies increased with age. Ear pigmentation was detected in a 20-year-old woman implying ochronosis can start in patients before the age of 20. Gait and qAKUSSI were outside the normal range in all the patients with AKU. Conclusions: Ochronosis can be present before age 20 years.